Cascade Catalysis Through Bifunctional Lipase Metal Biohybrids for the Synthesis of Enantioenriched O‐Heterocycles from Allenes. Issue 16 (22nd June 2022) - Naapuri, Janne M.; Losada‐Garcia, Noelia; Rothemann, Robin Alexander; Pichardo, Manuel Carmona; Prechtl, Martin H. G.; Palomo, Jose M.; Deska, Jan
Abstract: Lipase/metal nanobiohybrids, generated by growth of silver or gold nanoparticles on protein matrixes are used as highly effective dual‐activity heterogeneous catalysts for the production of enantiomerically enriched 2, 5‐dihydrofurans from allenic acetates in a one‐pot cascade process combining a lipase‐mediated hydrolytic kinetic resolution with a metal‐catalyzed allene cycloisomerization. Incorporating a novel strategy based on enzyme‐polymer bioconjugates in the nanobiohybrid preparation enables excellent conversions in the process. Candida antarctica lipase B (CALB) in combination with a dextran‐based polymer modifier (DexAsp) proved to be most efficient when merged with silver nanoparticles. A range of hybrid materials were produced, combining Ag or Au metals with Thermomyces lanuginosus lipase (TLL) or CALB and its DexAsp or polyethyleneimine polymer bioconjugates. The wider applicability of the biohybrids is demonstrated by their use in allenic alcohol cyclizations, where a variety of dihydrofurans are obtained using a CALB/gold nanomaterial. These results underline the potential of the nanobiohybrid catalysis as promising approach to intricate one‐pot synthetic strategies. Abstract : Hybrid catalysts : Metal nanoparticles are deposited in a polymer‐modified protein framework to obtain bifunctional hybrid catalysts that combine the transition metal activities with the host biocatalysts′ activation mode. A tailor‐made lipase‐silver nanobiohybrid is successfully exploited in a cascade design where a racemic allenic acetate is transformed to an enantioenriched dihydrofuran via a sequential hydrolytic kinetic resolution and a cycloisomerization.